Living Arrangement and Perceived Stress Among 1st to 3rd Year Medical Students, Pamantasan ng Lungsod ng Maynila - 4 0 16; 5 (2010)
Significant levels of stress among medical students can cause physical and mental health problems, reduce self-esteem and affect academic performance. This study determined the association between living arrangement and the perceived stress among 1st, 2nd, and 3rd year Pamantasan ng Lungsod ng Maynila (PLM) medical students. Subjects were given questionnaires containing the perceived stress scale (PSS). Microsoft Excel 2007 and Epi Info version 6 were used for encoding and analysis. Odds ratio of the whole population (0.80) and each year level (1st year: 0.39; 2nd year: 1.13; 3rd year: 1.37) were computed using Epi Info version 6 Statcalc. Chi square test for homogeneity yielded a p-value of 0.64 (95% CI) for the whole population. The p-values for 1st, 2nd and 3rd year were 0.30, 0.87, 0.74, respectively. P-values for the whole population and for each year level were greater than 0.05, indicating that the population was homogenous. A wide range at 95% confidence interval for the whole population (0.28-2.26) and per year level (1st year: 0.04-3.01; 2nd year: 0.22-5.74; 3rd year: 0.17-12.70) demonstrated that living arrangement was not associated with perceived stress among PLM medical students.
Keywords: 2 -- 0; 6; 20; 20; 2